Actin cytoskeleton and the dynamics of immunological synapse - Mayya, V; Dustin, M (Springer Netherlands, 2010)
T lymphocytes traffic through tissues by different modes of amoeboid motility while scanning for antigenic peptides presented on the surface of Antigen-Presenting Cells (APCs). Effective T-Cell Receptor (TCR T Cell Receptor TCR) signaling, upon recognition of a peptide, leads to the formation of a cell-cell junction between the T lymphocyte and the APC Antigen Presenting Cell APC. This junction has been termed as the immunological synapse (when it is radially symmetric and stable) or as the immunological kinapse (when it is asymmetric and mobile). Well-regulated coordination between the migratory behavior of T cells and the dynamics of immunological synapse is important for all the major facets of adaptive immune response. In this chapter we discuss how the actin cytoskeleton mediates this coordination by serving as a crucial platform for integrating and influencing signals from the TCR T Cell Receptor TCR, adhesion and chemokine receptors. We also highlight key experimental approaches that have shaped our current understanding on the role of the actin cytoskeleton in the dynamics of the synapses and kinapses.